English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-02-19 03:28:34 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

30e(e^2 - 2e + 1) = 30e (e-1)(e-1)

2007-02-19 03:34:54 · answer #1 · answered by richardwptljc 6 · 0 0

Divide everything by 30e
30e(e^2-2e+1)
30e(e-1)(e-1)

2007-02-19 11:35:28 · answer #2 · answered by leo 6 · 0 0

30e^3 -60e^2 +30e = 30e (e^2 - 2e + 1) = 30e (e-1)(e-1)

2007-02-19 12:32:37 · answer #3 · answered by KASTA 2 · 0 0

=30e*(e^2 -2e+1) = 30e*(e-1)^2

2007-02-19 11:52:28 · answer #4 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers